Faktor-Faktor yang Mempengaruhi Perilaku Penggunaan Scaffolding di Proyek Gedung Kereta Api PT Istaka-Mina KSO - Siti Chujaimah; Herlina Herlina (STIKes Persada Husada Indonesia, 2022)
Scaffolding is a scaffolding or construction assistant for building work, scaffolding is made when the building work has reached a height of 2 meters and cannot be reached by workers. The purpose of this study was to determine the factors that influence the behavior of using scaffolding at PT Istaka-Mina KSO. The design of this research is an analytical research using a quantitative approach, with a cross sectional study, where the research subjects are workers who work using scaffolding in the PT Istaka-Mina KSO Railway East Bekasi project with a sample of 60 respondents obtained using the method Covenience Sampling using the Slovin formula (1960). Analysis of the data used in this research is univariate and bivariate using Chi Square. The results showed that there was a significant influence between knowledge and behavior with a P-value of 0.03 (<0.05) and the influence of attitude and behavior with a P-value of 0.05 (0.05). And the results that have no effect, namely age, education, length of working hours, years of service, PPE facilities, scaffolding facilities and supervision by HSE are not found to have a significant effect. Conclusion For PT Istaka-Mina KSO, behavior should be improved by more frequent socialization to workers about how to install scaffolding once every 2 weeks and conducting TBM (Toolbox meetings) so that workers' knowledge of the use of scaffolding is increased, not only briefly, must know more deeply about the safe and comfortable use of scaffolding